AN ACADEMIC PERSPECTIVE ON THE PRESENT STATE OF ENGLISH LANGUAGE INSTRUCTION IN UZBEKISTAN’S SECONDARY EDUCATION SYSTEM - Iroda Khamidova (XALQARO ILMIY-AMALIY ANJUMAN "TA’LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
Uzbekistan is taking a progressive approach to English language instruction to equip students with the essential skills and competencies needed for success in the 21st century. Foreign language specialists have made significant progress in implementing the objectives outlined in this Resolution. They have developed a new State Educational Standard along with teaching curricula and syllabuses. Additionally, numerous teaching aids are being created.